Neuroticism dan kecanduan pada game multiplayer online battle arena - Edy Surahman; Lukman Lukman; Muh. Nur Hidayat Nurdin (Fakultas Psikologi, 2022)
The increasing popularity of multiplayer online battle arena games that occurred resulted in negative impacts, one of which is internet gaming disorder. Some studies suggest that neuroticism is correlated with internet gaming disorder, but previous studies have provided inconsistent results. Moreover, research related to multiplayer online battle arena games is scarce, regardless of large popularity and community size. This study aims to determine the correlation of neuroticism with internet gaming disorder in multiplayer online battle arena. The sample in this study amounted to 67 online game users consisting of 49 men and 18 women who suffer from internet gaming disorder. Samples were obtained with purposive sampling technique. Data analysis using spearman rank correlation yielded results of r = 0.306 and p = 0.006. This shows that there is a positive correlation between neuroticism and internet gaming disorder. These results are expected to provide information about neuroticism and internet gaming disorder to online game users. Keywords: Internet gaming disorder, MOBA, neuroticism